Virtual Interviews Improve Equity and Wellbeing: Results of a Survey of Applicants to Obstetrics and Gynecology Subspecialty Fellowships - Ann Do Tran; Christine A. Heisler; Sylvia Botros-Brey; Hanzhang Wang; Bertille Gaigbe-Togbe; Ava Leegant; Anne Hardart (BMC Medical Education, 2022)
Abstract Background Nationwide restrictions and recommendations from the Association of American Medical Colleges mandated program directors to conduct all graduate medical education interviews virtually in the Spring of 2020 in response to the COVID-19 pandemic. This study was conducted to assess the impact of virtual interviews on a candidates’ ability to effectively create a rank list. Objective The primary objective of this study was to evaluate Obstetrics and Gynecology (ObGyn) subspecialty fellowship applicants’ perspectives regarding the effectiveness of virtual interviews for creating a rank list. Secondary outcomes included perceived advantages and disadvantages of the process and costs of the process. Methods This was a cross-sectional IRB-exempt study, using an electronic survey administered to a convenience sample of applicants to ObGyn subspecialty fellowship programs. The survey was administered via RedCap between the rank list submission deadline and the Match. Descriptive statistics were used. Results Response rate was 158/330 (48%). Overall, 129/158 (82%) percent of respondents felt confident in making their rank list based on the virtual interviews, and 146/158 (92%) were “very satisfied” or “somewhat satisfied” with the process. Of those who expressed an interview style preference, 65/149(44%) of respondents preferred virtual interviews; 49/149(33%) had no preference or were not sure. Nearly all 146/148(99%) applicants cited cost-savings as a distinct advantage of virtual interviews. Conclusion Applicants to ObGyn subspecialty fellowships felt comfortable to create a rank list based on the virtual interview. This study indicates that the virtual format is effective, less stressful and less costly for ObGyn subspecialty interviews and should be considered beyond the pandemic to remove barriers and burdens for applicants.